Acute elevations in serum hormones are attenuated after chronic training with traditional isoinertial but not accentuated eccentric loads in strength‐trained men. Issue 7 (10th April 2017) - Walker, Simon; Häkkinen, Keijo; Haff, Guy Gregory; Blazevich, Anthony J.; Newton, Robert U.
Abstract: It has been proposed that the maintenance of acute hormonal responses reveal an efficacy of a training stimulus to evoke ongoing increases in strength and muscle mass. We previously observed that maximum strength continued to improve throughout a 10‐week period in an accentuated eccentric loading group (AEL) but not a traditional isoinertial loading (ISO) group. Therefore, this study investigated whether the magnitude of acute hormonal responses was greater (i.e., maintained) in AEL compared to ISO at the end of the training period. Subjects in AEL (eccentric load = concentric load + 40%) and ISO performed experimental loading tests (three sets of 10 repetitions in the leg press and knee extension exercises) during weeks 2 and 9 of the training period. Blood samples collected during these experimental loadings were analyzed for serum testosterone, growth hormone and cortisol concentrations. Maximum isometric knee extension torque (MVC) and lower‐limb lean mass were assessed before and after 5 and 10 weeks of training. Acute testosterone, growth hormone and cortisol responses to traditional isoinertial loading were reduced at the end of the training period but were not reduced after accentuated eccentric load training ( P < 0.05‒0.1 between‐groups). Increases in MVC and lower‐limb lean mass over weeks 6‒10 were greater in AEL compared to ISO (MVC: 7.3 ± 5.4 vs. −0.4 ± 7.2%, P = 0.026 for between‐group difference; lower‐limb lean mass: 1.6 ± 2.2 vs. −0.2 ± 1.4%, P = 0.063 for between‐group difference). The maintenance of acute hormonal responses and continued strength gain in AEL but not ISO are consistent with the hypothesis that maintained acute responses indicate an efficacy of a training stimulus to evoke ongoing adaptation. However, since relationships between hormonal responses and training‐induced adaptations were not statistically significant, the data suggest that tracking of acute hormonal responses on an individual level may not provide a sensitive enough guide for decisions regarding program design and periodization. Abstract : Accentuated eccentric load provides a greater stimulus for adaptation in already strength‐trained men over a prolonged period of time. This prolonged efficacy to induce adaptation is reflected by the maintained acute endocrine response at the end of the training period. Traditional strength training methods demonstrate a blunted acute hormone response after training and may require more frequent programming changes.